Analysis of Project Monitoring Practices on Implementation of Road Construction in Rwanda. A Case of Sonatube -Bugesera Road - Theogene, MUPENDE (International Journal of Scientific Research and Management (IJSRM), 2023)
The general objective of the study was to analyze the effect of project monitoring practices on implementation of road construction projects in Rwanda. The study was carried out in Kigali, Rwanda, Kicukiro-Bugesera Road. This study was guided by the following specific objectives; determine the effect of communication, determine the effect of monitoring tools, investigate the influence of stakeholder’s participation, establish the effect of staff competency on implementation of road construction projects in Kigali. The research study adopted a descriptive research design targeting 84 project managers, committee members and monitoring committee. A closed ended structured questionnaire will be used to collect primary data from 84 sampled respondents. A pilot study was conducted to ascertain the reliability and validity of the instruments. The quality and consistency of the study was further assessed using Cronbach’s alpha. Data analysis was performed using Statistical Package for Social Science (SPSS) version 23. Data presentation was done using frequency counts, percentages, means, standard deviations, regression, correlation and the information were presented in form of tables. The findings revealed that 52.4% of the respondents strongly agreed that project monitoring tools affects implementation of road construction projects in Rwanda. 41.7% of the respondents agreed, with 0% of the respondent remaining neutral. 5.9 % disagreed and none strongly disagreed. This indicates that the majority of the respondent at 52.4% considers that project monitoring tools affects Project implementation of road construction projects in Rwanda. The study findings revealed that for monitoring processes to function properly it requires management support as a mediating factor for a project to succeed. The study recommends management should give their support to all levels of stakeholders for projects to succeed.Key Words: Communication, Monitoring Tools, Stakeholder’s Participation, Staff Competency.